Aluminum‐Catalyzed Hydroalkoxylation at Elevated Temperatures: Fast and Simple Access to Coumarans and Other Oxygen Heterocycles. Issue 11 (16th August 2013) - Schlüter, Johannes; Blazejak, Max; Hintermann, Lukas
Abstract An aluminum‐catalyzed intramolecular hydroalkoxylation of nonactivated alkenes is presented as a powerful synthetic tool for the preparation of oxygen heterocycles, which are of major interest for the preparation of biological and pharmaceutical active compounds. The aluminum isopropoxide catalyzed (5 mol %) cyclization of 2‐allylphenols at elevated temperatures (250 °C, 20 min) provides 2‐methylcoumarans (2‐methyl‐2, 3‐dihydrobenzofuran) in an exceptionally fast, simple, and economic manner. Moreover, heating of allyl aryl ethers with aluminum isopropoxide (5 mol %) gives 2‐methylcoumarans by a tandem Claisen rearrangement–hydroalkoxylation reaction. For either reaction, the catalyst tolerates a broad scope of substrates with various functional groups. By using the weakly electrophilic aluminum alkoxide as the catalyst, occurrence of "hidden Brønsted acid" catalysis can be excluded under the present reaction conditions.